The impact of social networking sites on the lives of individuals within Palestinian society during the period 2015-2020 "Afield study applied to the residents of Bethlehem – Palestine" - Alawneh, Abdelmajid Nayif (Journal of Humanities & Social Sciences, 2020)
The aim of this research is to determine the extent of the impact resulting from electronic social networking sites with their various indicators on the lives of members of the Palestinian society in all aspects of living. The researcher has used the descriptive analytical method and the questionnaire tool in collecting field data, as the research community was a resident of the Palestinian city of Bethlehem located south The West Bank from all aspects of life and living for them, and the sample taken from the research community reached (888) individuals, with a percentage (3%) of the entire research community, and this research has reached a set of important results on this topic, one of the most important being that most users The reality of social media are from the young category, and that the most used website is Facebook compared to jealousy, as it turns out that the most affected aspects of life from electronic social networking sites are the social aspect, whose impact ratio has reached a value (1.90%) followed by the religious side, which came The percentage of being affected by social media has reached a value of (3.87%), then came the educational aspect, which has reached an impact rate of (4. 83%), then the behavioral aspect came with an impact rate of (3. 81%) then, culturally, at a value of (78%), as for the psychological aspect, which reached a value of 2.63%), another and the lowest of these values ​​came to the economic aspect, which reached a value (9.58%), thus forming the least effects resulting from the existence and use of sites. Electronic social networking within the Palestinian society. As for the nature of the relationship between social media and the aspects of life for members of Palestinian society, a strong and statistically significant relationship has emerged, and the nature of this relationship came in a direct way between each of the subscription period, the number of hours of daily use, the number of added friends, the goal of the subscription, and the number of sites The electronic system used and between the various aspects related to the life of the members of the Palestinian society represented in the social, religious, educational, behavioral, cultural, psychological and economic fields. At the end of the research, the researcher made a number of recommendations at the public and private levels that came from the most important of them. The time for awareness-raising by educational institutions represented in schools and universities to warn against the increase in the use of such sites and warn of the negative consequences resulting from them, and to identify the main issues in which the use of electronic social networking sites that are beneficial to the user are required, especially in social, behavioral, and other aspects.